Icelandic National Culture compared to National Cultures of 25 OECD member states using VSM94 - Guðmundsdóttir, Svala; Guðlaugsson, Þórhallur; Aðalsteinsson, Gylfi Dalmann (Stjórnsýslustofnun, 2015)
Researchers such as Hofstede (2002) and House, Hanges, Javidan, Dorfman and Gupta, (2004) have defined well-known cultural clusters such as, Anglo, Germanic, and Nordic cultural clusters. However, Iceland was not incorporated in these studies and therefore the research question of this paper is: In relation to Hofstede´s five cultural dimensions where does Iceland differ in relation to 25 of the OECD member states using VSM94? A questionnaire was sent to students at the University of Iceland, School of Social Sciences by e-mail in October 2013. The five dimensions of national culture were measured using scales developed by Hofstede called VSM 94. The results indicated that Iceland differs considerably from nations such as Slovakia, Japan, India, Thailand and China, which were found high in PDI and the MAS dimension while Iceland was found to be high in IDV and low in PDI. When considering the 25 OECD countries, Iceland is more similar to the Anglo cluster, C3, Canada, New Zealand, United Kingdon, Australia and United States than the Nordic cluster, C1 i.e. Denmark, Sweden and Norway. Iceland is similar to those countries in relation to high IDV, low PDI but differs in the dimensions MAS and UAI where Iceland scores higher.